Reduction of Management Costs and Avoidance of Air Release of Carcinogens Through a Waste Segregation Program in a Brazilian Medical Institution - Cesario, Fabiane Kellem Oliveira; Fontoura, Renata Pereira; da Conceição Junior, Amarildo Henrique; Cruz, Amanda Gentil; Nimer, Nidah Fawzi Said; Morais, Poliana Brito; Omena, Brenda Monteiro; dos Santos, Edivaldo Bazilio; Silvestrini, Anderson Arantes; Andrade, Rosângela Vieira (Frontiers in Public Health, 2020)
Hospital waste management is a current sustainability challenge. Although not always performed, the most applied approach in current protocols is the proper segregation of waste. The incineration of hospital waste is an important source of emission of specific toxic particles and gases. We highlighted dioxins, whose representatives have been considered carcinogenic agents since 1994. Dioxins exposure was associated with greater cancer morbidity and mortality in several experimental and epidemiologic studies. In the present study, we presented the impact of a hospital waste management program implemented in an oncology institution based on proper segregation and consequent reduction of incinerated mass. Data were collected for eight years and the waste was separated into five categories: infectious (A4), chemical (B), recyclable (DR), non-recyclable (DNR) and sharps (E). The classes addressed to incineration were A4, B, and E. A team education starting from the admission process and with a continued education program was essential for a successfully implemented program. We achieved a 66% saving of waste from incineration, equivalent to 76 tons, of which 71.9 tons corresponded to recyclable waste. If the waste separation protocol was not implemented, the biohazardous and chemical material would contaminate the rest of the residues, making incineration as a final destination mandatory for all the waste. This scenario would result in significantly more dioxins release and a 64% higher cost of waste management. This low-cost implementation measure was effective in the cost reduction of waste management and minimization of air release of human carcinogens.